Comprehensive Review on Postoperative Nausea and Vomiting Following General Anesthesia - Deepanshu Sharma; Aniyat Sheikh; Seema Rani; Gagandeep Singh; Atul Khajuria (International Journal of Advance in Molecular Engineering, 2024)
Postoperative nausea and vomiting, often known as PONV, is a common and uncomfortable consequence that occurs after general anesthesia. Patients of all ages are susceptible to experiencing this condition. Even though there have been advances in anaesthesia procedures and treatments, postoperative nausea and vomiting (PONV) continues to be a serious concern since it has the potential to cause patients to experience discomfort, delay their recovery, extend their hospital stays, and increase the expenses of healthcare. In this study, we will attempt to provide a full overview of PONV, covering topics such as its pathogenesis, risk factors, preventative tactics, and therapeutic choices. It is possible for anesthesiologists and other healthcare providers to improve surgical outcomes and maximize patient care by gaining an understanding of the mechanisms that underlie postoperative nausea and vomiting (PONV) and putting evidence-based therapies into practice.
Keywords: Anesthesia complications; PONV risk factors and prevention; pathogenesis of PONV; postoperative nausea and vomiting (PONV); therapeutic approaches in PONV